Diversity and Plant Growth-Promoting Ability of Endophytic, Halotolerant Bacteria Associated with Tetragonia tetragonioides (Pall.) Kuntze - Dilfuza Egamberdieva; Jakhongir Alimov; Vyacheslav Shurigin; Burak Alaylar; Stephan Wirth; Sonoko Dorothea Bellingrath-Kimura (Plants, 2021)
The diversity of salt-tolerant cultivable endophytic bacteria associated with the halophyte New Zealand spinach (Tetragonia tetragonioides (Pall.) Kuntze) was studied, and their plant beneficial properties were evaluated. The bacteria isolated from leaves and roots belonged to Agrobacterium, Stenotrophomonas, Bacillus, Brevibacterium, Pseudomonas, Streptomyces, Pseudarthrobacter, Raoultella, Curtobacterium, and Pantoea. Isolates exhibited plant growth-promoting traits, including the production of a phytohormone (indole 3-acetic-acid), cell wall degrading enzymes, and hydrogen cyanide production. Furthermore, antifungal activity against the plant pathogenic fungi Fusarium solani, F. oxysporum, and Verticillium dahliae was detected. Ten out of twenty bacterial isolates were able to synthesize ACC deaminase, which plays a vital role in decreasing ethylene levels in plants. Regardless of the origin of isolated bacteria, root or leaf tissue, they stimulated plant root and shoot growth under 200 mM NaCl conditions. Our study suggests that halophytes such as New Zealand spinach are a promising source for isolating halotolerant plant-beneficial bacteria, which can be considered as potentially efficient biofertilizers in the bioremediation of salt-affected soils.